2015
DOI: 10.1016/j.neulet.2014.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Arithmetic memory networks established in childhood are changed by experience in adulthood

Abstract: Adult bilinguals show stronger access to multiplication tables when using the language in which they learned arithmetic during childhood (LA+) than the other language (LA−), implying language-specific encoding of math facts. However, most bilinguals use LA+ throughout their life, confounding the impact of encoding and use. We tested if using arithmetic facts in LA− could reduce this LA− disadvantage. We measured event related brain potentials while bilingual teachers judged the correctness of multiplication pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 32 publications
2
25
1
Order By: Relevance
“…Given that any potentially meaningful stimulus can elicit an N400 ( Kutas and Hillyard, 1980 ), including numbers represented as digits ( Dickson and Federmeier, 2018 ), it is probable that the adults generated small N400 s to every digit as they appeared. Indeed, under the right circumstances, namely when the problems can be treated like language, adults can elicit robust N400 effects to multiplication problems ( Dickson et al, 2018 ; Martinez-Lincoln et al, 2015 ; Salillas and Wicha, 2012 ). However, the contribution of the N400 generated by each digit on the ERP waveform morphology, and on the correctness effect itself, appears to be negligible in this and other studies (see Dickson and Federmeier, 2017 ; Jasinski and Coch, 2012 ).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Given that any potentially meaningful stimulus can elicit an N400 ( Kutas and Hillyard, 1980 ), including numbers represented as digits ( Dickson and Federmeier, 2018 ), it is probable that the adults generated small N400 s to every digit as they appeared. Indeed, under the right circumstances, namely when the problems can be treated like language, adults can elicit robust N400 effects to multiplication problems ( Dickson et al, 2018 ; Martinez-Lincoln et al, 2015 ; Salillas and Wicha, 2012 ). However, the contribution of the N400 generated by each digit on the ERP waveform morphology, and on the correctness effect itself, appears to be negligible in this and other studies (see Dickson and Federmeier, 2017 ; Jasinski and Coch, 2012 ).…”
Section: Discussionmentioning
confidence: 62%
“…Research using ERPs to study how arithmetic is processed has revealed robust brain responses to proposed solutions in both children and adults. This research has been dominated by studies that include adult populations ( Dickson et al, 2018 ; Dickson and Federmeier, 2017 ; Jasinski and Coch, 2012 ; Jost et al, 2003 ; Martinez-Lincoln et al, 2015 ; Niedeggen et al, 1999 ; Núñez-Peña et al, 2006 ; Salillas and Wicha, 2012 ), with a smaller group of studies that have compared child and adult brain responses ( Moore et al, 2014 ; Prieto-Corona et al, 2010 ; Xuan et al, 2007 ; Zhou et al, 2011 ). The methods used in these studies have varied, with some using verification tasks and others production, or different operations (addition vs multiplication, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…However, numerical expressions presented in Arabic digits elicit a difference driven primarily (if not solely) by a prominent positive amplitude modulation for correct solutions, rather than a modulation of the negative-going N400 (Dickson & Federmeier, 2017; Jasinski & Coch, 2012). In fact, most experiments using digits, and even some using number words, appear to feature the positivity in response to correct solutions (Bassok et al, 2009; Fisher et al, 2010; Guthormsen et al, 2016; Martinez-Lincoln, Cortinas, & Wicha, 2015; Salillas & Wicha, 2012; Szűcs & Csépe, 2004), but this positivity has not been reported as such in most of these studies. Avancini, Soltész, and Szűcs (2015) acknowledge the presence of positivities for both correct and incorrect solutions, but oddly argue that a latency shift between them resulted in the emergence of the “N400-like” response.…”
Section: Introductionmentioning
confidence: 96%
“…In the present study, we will observe for the first time the unbalance for numerical wording systems in balanced bilinguals. It has already been shown that bilinguals have a preference for one of their two codes in arithmetic representations (Martinez-Lincoln et al 2015;Salillas and Wicha 2012;Spelke and Tsivkin 2001) and more recently it has been shown that LL math might be the language of preference for accessing magnitude (Salillas et al 2015;Salillas and Carreiras 2014). This preference is proposed to take place during early math learning.…”
Section: Bilingualism and Code-switchingmentioning
confidence: 99%
“…These studies have also permitted a deep look at the role played by language in our math system. Based on current evidence, it is assumed that mathematical development in bilinguals normally involves one of the two languages preferentially (Bernardo 2001;Grabner et al 2012;Martinez-Lincoln et al 2015;Salillas et al 2015;Salillas and Wicha 2012). It is also well-known that bilinguals often translate or switch languages when carrying out simple arithmetic facts or for mathematical thinking in general (Moschkovich 2007).…”
Section: The Link Between Language and Numbersmentioning
confidence: 99%